Climate Finance : Engaging the Private Sector - Patel, Shilpa (World Bank, Washington, DC, 2017)
This paper is focused on climate-related investment in developing countries. It provides the reader with an overview of climate-related activities, clarifies the terminology and discusses the sources of finance and public support. Section 1 gives an overview of current investment in climate-related activities. Section 2 defines a typology of private sector investment according to stage of technology development and type of project/investment. Section 3 outlines the risks faced by a private investor in emerging markets, how these risks are typically mitigated, and discusses how barriers to low carbon investment can exacerbate these risks. Section 4 discusses the different types of support relevant for the private sector and, building on the experience of the EBRD and IFC, the leverage associated with the different project types and support sources. Case studies of innovative use of concessional finance are also provided. Section 5, using the two main available sources of information, assesses the level of investment that will be required for a 2 degrees celsius pathway and concludes with a description of the support mechanisms that will be needed to mobilize private flows. An annex provides a list of interesting initiatives being implemented by other intergovernmental organizations and agencies that also speak to improving private sector engagement in the climate investment space.